2018
DOI: 10.2147/nss.s127475
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disturbances in women with polycystic ovary syndrome: prevalence, pathophysiology, impact and management strategies

Abstract: Polycystic ovary syndrome (PCOS) is a complex endocrine disorder affecting the reproductive, metabolic and psychological health of women. Clinic-based studies indicate that sleep disturbances and disorders including obstructive sleep apnea and excessive daytime sleepiness occur more frequently among women with PCOS compared to comparison groups without the syndrome. Evidence from the few available population-based studies is supportive. Women with PCOS tend to be overweight/obese, but this only partly accounts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(72 citation statements)
references
References 191 publications
(225 reference statements)
0
54
0
5
Order By: Relevance
“…The findings of an independent relationship between PCOS and sleep disturbance after adjustment for factors such as BMI and depression raise the hypothesis that PCOS status per se may be involved in disrupting sleep. The exact physiological mechanisms and directionality of such a relationship could involve several possibilities . Insulin resistance is a key feature of PCOS, and cross‐sectional studies have reported that diabetes was strongly associated with excessive daytime sleepiness .…”
Section: Discussionmentioning
confidence: 99%
“…The findings of an independent relationship between PCOS and sleep disturbance after adjustment for factors such as BMI and depression raise the hypothesis that PCOS status per se may be involved in disrupting sleep. The exact physiological mechanisms and directionality of such a relationship could involve several possibilities . Insulin resistance is a key feature of PCOS, and cross‐sectional studies have reported that diabetes was strongly associated with excessive daytime sleepiness .…”
Section: Discussionmentioning
confidence: 99%
“…There is also a growing body of evidence suggesting that sleep disturbances including obstructive sleep apnea (OSA) and excessive daytime sleepiness can be added to the list of cardiometabolic risk factors in PCOS with link between the two being complex and possibly bidirectional ( 40 , 41 ). OSA is a relatively common and chronic sleep disorder characterized by recurrent complete (apnea) or partial (hypopnea) upper airway obstruction during sleep leading to intermittent hypoxia, cortical microarousals, sleep fragmentation, increased sympathetic neural activity, hypothalamus–pituitary–adrenal axis dysregulation, altered cytokine release and oxidative stress ( 42 ).…”
Section: Insulin Resistance Metabolic Syndrome Obesity and Sleep DImentioning
confidence: 99%
“…Polycystic ovary syndrome (PCOS) and obstructive sleep apnoea (OSA) are associated with obesity and commonly coexist. 1,2 The underlying mechanisms that link PCOS and OSA include insulin resistance, hormonal disturbances, oxidative stress and sympathetic overactivity. 1 A recent systematic review and meta-analysis showed that around a third of women with PCOS may suffer from OSA, 3 while population-based cohort studies suggest higher incidence of OSA in women with PCOS compared with controls.…”
Section: Introductionmentioning
confidence: 99%